Rattus nitidus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Rattus nitidus (Hodgson, 1845). Ann. Mag. Nat. Hist., 15: 267. TYPE LOCALITY: Nepal. DISTRIBUTION: Nepal; Thailand; W. Burma; Kansu and Kiangsu to S. China; Philippines; introduced in N.W. New Guinea and Sulawesi (Indonesia). COMMENT: Includes vanheurni, manuselae (see Musser, 1973, Am. Mus. Novit., 2511:1-30, and Musser, 1981, Bull. Am. Mus. Nat. Hist., 169(2): 122), Mus guhai (see Marshall, 1977, Bull. Am. Mus. Nat. Hist., 158(3):210), and subditivus (see Musser, 1971, Am. Mus. Novit., 2454:119). Calaby and Taylor, 1980, Zool. Meded., 55:215-219, considered ruber a junior synonym of nitidus, and the next available name for the forms that were formerly included in ruber is praetor. ISIS NUMBER: 5301410011058080001 as R. nitidus. 5301410011058098001 as R. ruber. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 5), pp. 504-560 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 551, DOI: 10.5281/zenodo.7353037